THE CONCEPT OF INTEGRATION OF SCIENCE AND RELIGION - Neneng Munajah (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
The idea of ​​integrating science and religion continues to resonate in the Islamic world. This idea becomes an alternative for the development of Islamic scholarship, and will break the ice that still surrounds the Islamic world. Because of its problematic nature, the responses and responses of Muslim scholars to the idea have varied greatly. There are pros and cons, some Muslim scientists support it, and some reject it. This article uses a qualitative method and uses a variety of literature to explain the background of the importance of the concept of integrating science and religion, as well as discussing the model or its form. Gagasan mengenai Integrasi ilmu dan agama, tetap menggema di dunia Islam. Gagasan tersebut menjadi alternative bagi pengembangan keilmuan Islam, dan akan mendobrak kebekukan yang kini masih menyelimuti dunia Islam. Karena sifatnya yang problematis, maka tanggapan dan respon cendekiaan Muslim terhadap gagasan tersebut, menjadi sangat beragam. Ada yang pro dan kontra, sebagian ilmuan Muslim mendukungnya, dan sebagian yang lain menolaknya. Artikel ini menggunakan metode kualitatif dan menjadikan beragam literature untuk menjelaskan latar belakang pentingnya konsep integrasi ilmu dan agama, juga mengetengahkan tentang model atau bentuknya.